(untitled) (Materiali di Estetica. Terza serie, 2024)
Emotions encompass biological, psychological, and social aspects that shape the human experience. They are not merely reactions to eliciting events but guide choices, motivate behavior, and influence interpersonal relationships. Within this framework, defining negative emotions is highly complex. Every emotion, including fear or anger, serves a specific function that contributes to individual survival and adaptation. What may be problematic is not the emotion itself but rather how it is experienced, regulated, and evaluated, both individually and socially. Artistic experience is closely tied to the emotional valence of a stimulus and, in recent years, to the brain mechanisms underlying aesthetic behavior. Negative emotions play a crucial role in both the creation and appreciation of art. Furthermore, differences in emotional behavior and artistic engagement are also reflected at the neural level, shaping the scope of a new field of study: neuroaesthetics.